Experimental studies on the rain noise of lightweight roofs: Natural rains vs artificial rains. (May 2016) - Yan, Xiang; Lu, Shuai; Li, Junjie
Highlights: Experiments on rain noise caused by natural and artificial rains are conducted. The relationship between A level of natural rain noise and rain intensity is shown. Deviation between actual rain noise and laboratory measurement is quantified. Method to predict actual rain noise using laboratory measurement results is provided. Abstract: Rain noise is often an unpleasant problem that disturbs people's activities significantly in buildings with lightweight roofs, however, the existing researches are all based on artificial rains in laboratory, while the characteristics of natural rain noise as well as the relationship between actual rain noise and laboratory measurements still need to be explored to fulfill practical demands. This paper first presents two experiments on natural rain noise, revealing that rain intensity is the decisive factor of natural rain noise for heavy rains, and the A-weighted sound pressure level of rain noise caused by heavy rains is proportional to the logarithm of rain intensity. Furthermore, three more experiments on the rain noise with artificial rains are carried out, indicating that differences in rain intensities, fall heights and raindrop size distributions are the factors that cause significant deviation between actual rain noise and laboratory measurements. This total deviation as well as the deviations caused by each factor are then quantified. Finally, a method to predict the actual rain noise of a certain roof using laboratory measurement results is provided, which can be useful in real projects as an effective substitute of experiments using uncontrollable real rains.